Analysis of Educatonal Qualification Grade of Preschool Teachers in Western Europe: Strategy of Ukrainian Professional Training System Reformation - Melnyk, Natalia (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
The article analyzes the peculiarities of preschool teachers’ professional training in West European countries. Educational qualification grades and specialties, which are awarded to graduates of higher education in the field of «Preschool Education» are characterized. The requirements to the future preschool teachers’ training in Europe and their influence on teachers’ educational system in Western Europe are presented in the issue. The analysis of the mentioned aspects enabled the determination of appropriateness and necessity of studying the educational qualification grades of foreign universities characteristics in order to adapt them in Ukrainian higher pedagogical education system, that will provide effective transformation of the national higher pedagogical education to European standards of professional training.